Development of a Four-Tier Test with a Metacognitive Perspective Approach on the Topic of Newton's Laws - Subali, Bambang; Widayati, Niken Tri; Sekarningtias, Felia Oktaviana; Wiyanto, Wiyanto; Ellianawati, Ellianawati; Siswanto, Siswanto (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aimed to develop a learning evaluation instrument on Newton's Law Materials using a four-tier test with a metacognitive perspective to identify students' thinking abilities from metacognition and students' misconceptions. The research employed the R&D (Research and Development) design with a 4-D development model (define, design, develop, and disseminate). The instrument was constructed by developing twelve questions. There were ten valid and reliable questions with good quality parameters (difficulty level and differentiating power). The researchers analyzed the four-tier test instrument with a metacognitive perspective approach using item difficulty level analysis, item discriminatory analysis, test reliability analysis, and expert validity testing. This research involved 30 participants in the small-scale test and 250 participants in the large-scale trial. The test results showed that the ten questions could identify students' thinking abilities from the perspective of metacognition and misconceptions on Newton's Law material. The findings of the large-scale test showed that students' thinking skills were mapped into high, medium, and low categories. Students' misconceptions were also mapped on each indicator of the questions compiled. Based on the mapping result, the highest students' misconceptions were found in the aspect of the metacognitive experience, with an average of 76 percent of students experiencing misconceptions.